Solid state fermentation for poly (L-lactide)-degrading enzyme production by Laceyella sacchari LP175 in aerated tray reactor and its hydrolysis of poly (lactide) polymer - Thanasak Lomthong,; Atsadawut Areesirisuk,; Sutthawan Suphan,; Titiporn Panyachanakul,; Sukhumaporn Krajangsang,; Vichien Kitpreechavanich, (Agriculture and Natural Resources, 2021)
Poly(L-lactide) (PLLA)-degrading enzyme was produced by Laceyella sacchari LP175 under solid state fermentation in a static tray reactor using agricultural products of cassava chips and soybean meal as the substrate. The maximum enzyme production was obtained at 518 ± 8.5 U/g dry solid after cultivation at 50°C in moistened air with an aeration rate of 0.8 L/min for 24 hr followed by no aeration for 48 hr. Enzyme production increased with discontinuous aeration under solid state fermentation by maintaining the cultivation moisture content at a high temperature. Crude enzyme extracted from the fermented solid substrate was optimized at pH 9.0 and using 0.2 M of Tris-HCl buffer concentration for degradation of 100 g/L PLA polymer film, yielding 63.00 ± 4.59% after incubation at 50°C for 48 hr. Scaled-up hydrolysis in a 2.0 L stirrer batch reactor produced maximum degradation of 68.00 ± 2.5% at an agitation rate of 200 rpm. Enzyme production by L. sacchari LP175 in the aerated tray reactor was improved using agricultural products as substrates and hydrolysis of PLA polymer film at high concentration was enhanced, showing the method’s potential for industrial application in the future.